Pelatihan, Motivasi Dan Kompensasi Pengaruhnya Terhadap Kinerja Karyawan (Studi PT. Bank XXX Kota Malang) - Alfi Nur Rohmaniya; Hadi Sunaryo; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThe purpose of this study was to describe the training, motivation, compensation and performance of employees and to analyze the effect of training, motivation, compensation on employee performance. This type of research is explanatory research. The population in this study were all employees of PT. Bank XXX Malang City Service, Operations and Support section totaling 61 people and the sample used is a saturated sample, namely all employees of PT. Bank XXX Malang City Service, Operations and Support. The data analysis method used multiple linear regression analysis. The results showed that training, motivation and compensation had a significant effect on employee performance either simultaneously or partially. Keywords: Training, Motivation, Compensation and Employee Performance